(untitled) (Polifonia, 2015)
Neste artigo, analisamos como o “estrangeiro” é significado em dicionários de língua portuguesa publicados em Portugal e no Brasil. Sob a perspectiva teórica da História das Ideias Linguísticas e da Análise de Discurso, visamos compreender quais sentidos são formulados para o “estrangeiro” no processo de constituição do espaço nacional brasileiro. Os resultados do trabalho apontam que, mesmo quando as definições formuladas para os verbetes parecem repetitivas, elas formulam discursos diferentes, conformados pelas condições sócio-históricas da época em que foram produzidos. PALAVRAS-CHAVE: estrangeiro, dicionário, Análise de discurso THE FOREIGNER IN PORTUGUESE LANGUAGE DICTIONARIES: SUBJECT, LANGUAGE AND SPACE ABSTRACT: In this article we analyse how the foreigner is meant in Portuguese language dictionaries published in Portugal and in Brazil. Considering the History of linguistic ideas and the Discourse Analysis theoretical perspectives, we aim to understand which senses are formulated for the foreigner in the constitution of the Brazilian national space. The results of this study show that even when the definitions formulated for the entries seem to be repetitive, they formulate different discourses, according to the socio-historical conditions of the time when they were produced. KEYWORDS: foreigner, dictionary, Discourse Analysis